Risk factors associated with 90-day recurrent stroke in patients on dual antiplatelet therapy for minor stroke or high-risk TIA: a subgroup analysis of the CHANCE trial - Wangqin, Runqi (Stroke Vasc Neurol, 2017)
OBJECTIVE: Many patients receiving dual antiplatelet therapy still had recurrent strokes. We aimed to identify factors associated with recurrent stroke at 90 days in patients receiving dual antiplatelet therapy in Clopidogrel in High-risk patients with Acute Non-disabling Cerebrovascular Events trial. METHODS: Patients with transient ischaemic attack or minor stroke receiving clopidogrel and aspirin in the trial were analysed in the study. The primary outcome was recurrent stroke within 90 days after the index event. Cox proportional hazard model with backward selection was used to identify factors associated with stroke. RESULTS: Among 2584 patients, 212 (8.2%) had a recurrent stroke, 216 (8.4%) had a composite of stroke, myocardial infarction, or vascular death and 204 (7.9%) had ischaemic stroke within 90 days. Multivariate analysis identified the following factors associated with stroke: history of hypertension with poor blood pressure control (HR, 1.92; 95% CI 1.22 to 3.03), the high baseline National Institute of Health Stroke Scale (NIHSS) score of 2 and 3 (2.12 (1.07 to 4.21) and 4.11 (2.05 to 8.22), respectively), time from onset to randomisation of <12 hours (1.47 (1.12 to 1.94)), the lipid-lowering therapy (0.61 (0.47 to 0.83)), the open-label aspirin dose at day 1 of ≥300 mg (1.98 (1.45 to 2.69)). Intracranial arterial stenosis (ICAS) was significantly associated with stroke in the sensitivity analysis (2.17 (1.16 to 4.04)). CONCLUSIONS: The high baseline NIHSS score, hypertension with poor blood pressure control, ICAS, time from onset to randomisation of less than 12 hours and no lipid-lowering therapy were associated with stroke, suggesting that patients with identified predictors still remain to be at high risk of recurrent stroke although being under the dual antiplatelet therapy. TRIAL REGISTRATION NUMBER: http://clinicaltrials.gov/show/NCT00979589. ClinicalTrials.gov number: NCT00979589